REDES DO COMÉRCIO DE RUA DE SALVADOR, BAHIA - Maia, Ana Cláudia Nogueira [UNESP] (Universidade Federal do Ceará, 2015)
This present paper reports a case study of the street trading in the central area of Iguatemi and Lima e Silva Avenue, Salvador – State of Bahia. While traversing the streets, it was possible to notice the diversity that this activity presents, the variety of goods, clothing, electronics, food products and those that are meant to meet a need momentary. The authors seek to understand the course that this diversity of goods conducts, from production to consumption, for this, the ‘foreign’ goods and clothes were analyzed in an attempt to track the entire way traced by those goods. Thus, a comprehension about possible networks formed behind the street trading were developed, in other words, the supply networks of this trade.

Este trabajo representa un estudio de caso de comercio de la calle que se produce en la Centralización Iguatemi y Avenida Lima e Silva, en Salvador, Bahia. Al caminar por las calles es la diversidad notable que esta actividad presenta son bienes de todo tipo, ropa, electrónica, productos alimenticios y los que están diseñados para satisfacer una necesidad momentánea. Buscamos entender el camino que lleva a la diversidad bienes desde la producción hasta el consumo, se analizan los productos de “extranjero” en un intento de controlar todo el trayecto del camino para ellos. Por lo tanto, desarrollamos un entendimiento en torno a redes posibles formados detrás de la venta ambulante, es decir, las redes de suministro de este comercio.

O presente trabalho representa um estudo de caso sobre o comércio de rua que ocorre na Centralidade do Iguatemi e na Avenida Lima e Silva, em Salvador-Bahia. Ao andarmos pelas ruas é perceptível a diversidade que esta atividade apresenta, são mercadorias de todos os tipos, roupas, eletrônicos, produtos alimentícios e aqueles que têm a função de suprir uma necessidade momentânea. Buscamos a compreensão do percurso que essa diversidade de mercadorias realiza, da produção ao consumo, para isso analisamos as mercadorias “estrangeiras” na tentativa de acompanhar todo o caminho traçado por elas. Assim, desenvolvemos a compreensão em torno de possíveis redes formadas por trás do comércio de rua, ou seja, as redes de abastecimento deste comércio.
nets trade street of Salvador, State Bahia
Keywords: Networks; Street trading; Goods; Circulation-distribution-consuption; Redes; Comércio de rua; Mercadoria; Circulação-distribuição-consumo